A clinical role of staging laparoscopy in patients with radiographically defined locally advanced pancreatic ductal adenocarcinoma - Satoi, Sohei (World J Surg Oncol, 2016)
BACKGROUND: The aim of current study is to verify usefulness of staging laparoscopy (stag-lap) for patient’s selection and to find prognostic factors in patients with radiographically defined locally advanced (RD-LA) pancreatic ductal adenocarcinoma (PDAC). METHODS: The LA disease was defined as an unresectable disease without distant organ metastasis based on resectability status of NCCN guideline in this study. Stag-lap was performed in 67 patients with RD-LA (2007–2012) which were divided into 4 groups according to metastatic site: group CY (peritoneal fluid or washing cytology positive and without any distant organ metastasis); group P (peritoneal dissemination); group L (liver metastasis); group LA (peritoneal fluid or washing cytology negative and without any distant organ metastasis). Clinical backgrounds, survival curves, and prognostic factors were investigated. RESULTS: There were 16 patients in CY group (24 %), 13 patients in P group (19 %), 10 patients in L group (15 %), and 28 patients in LA group (42 %). Median survival time was 13 months in CY group and 11 months in LA group, which was significantly better than 7 months in P group, respectively (p < 0.05). The rate of emergence of ascites in LA was significantly better than in CY or P groups (p < 0.05). Multivariate analysis showed that the presence of partial response and administration of second-line chemotherapy were significantly independent prognostic factors. CONCLUSIONS: The majority of PDAC patients with RD-LA had occult distant organ metastasis. Clinical features and survival curves were different depending on the site of occult distant organ metastasis. Administration of second-line chemotherapy and responsiveness to chemotherapy were associated with favorable prognosis. Staging laparoscopy should be routinely performed in patients with RD-LA PDAC (UMIN000019936).